Pengaruh Motivasi Belajar Terhadap Kemampuan Berpikir Kritis Matematis Siswa SMP Pada Materi Sistem Persamaan Linear Dua Variabel - Triyono, Bayu Agus (Polinomial : Jurnal Pendidikan Matematika, 2025)
This study aims to investigate the relationship between students’ mathematical critical thinking ability and their motivation to learn mathematics, specifically on the topic of Systems of Linear Equations in Two Variables (SPLDV) among junior high school students. The research employed a quantitative approach with a correlational method. The independent variable in this study is students’ motivation to learn mathematics, while the dependent variable is their mathematical critical thinking ability. The population consisted of junior high school students in Karawang Regency, and the sample comprised 33 students from a selected public junior high school using simple random sampling, ensuring each student had an equal opportunity to be selected as a participant. Data were analyzed using simple linear regression to examine the influence of learning motivation on students’ mathematical critical thinking ability. The findings indicate a positive and statistically significant relationship between students’ motivation to learn mathematics and their mathematical critical thinking ability. Specifically, learning motivation contributed 39.05% to students' critical thinking skills, with the remaining 60.95% influenced by other unexamined factors. These results underscore the pivotal role of learning motivation in enhancing students’ critical thinking in mathematics, particularly in the context of SPLDV. It is anticipated that these findings may serve as a valuable reference for educators in designing instructional strategies that simultaneously foster learning motivation and promote the development of mathematical critical thinking skills.